2019
DOI: 10.1088/1538-3873/aaf5ff
|View full text |Cite
|
Sign up to set email alerts
|

The Initial Conditions for Planet Formation: Turbulence Driven by Hydrodynamical Instabilities in Disks around Young Stars

Abstract: This review examines recent theoretical developments in our understanding of turbulence in cold, non-magnetically active, planetesimal forming regions of protoplanetary disks which we refer to throughout as "Ohmic zones". We give a brief background introduction to the subject of disk turbulence followed by a terse pedagogical review of the phenomenology of hydrodynamic turbulence. The equations governing the dynamics of cold astrophysical disks are given and basic flow states are described. We discuss the Solb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 168 publications
(319 reference statements)
2
61
1
Order By: Relevance
“…Variations of the viscosity parameter α in the 10 −4 -10 −2 range, which is commonly adopted for PSN models, show that the results are qualitatively close to those presented here and that the conclusions remain unchanged. The lowest value α = 10 −4 corresponds to the assumption of an MRI dead zone in our simulation box [45][46][47]. Our results are quite different from those derived by Ali-Dib et al [15] who found very high abundances of solid CO in the vicinity of its iceline.…”
Section: Resultscontrasting
confidence: 84%
“…Variations of the viscosity parameter α in the 10 −4 -10 −2 range, which is commonly adopted for PSN models, show that the results are qualitatively close to those presented here and that the conclusions remain unchanged. The lowest value α = 10 −4 corresponds to the assumption of an MRI dead zone in our simulation box [45][46][47]. Our results are quite different from those derived by Ali-Dib et al [15] who found very high abundances of solid CO in the vicinity of its iceline.…”
Section: Resultscontrasting
confidence: 84%
“…In Fig. 13, we compare the critical timescale of the VSI with the thermal relaxation timescale as described in Lin & Youdin (2015) and adopted by Malygin et al (2017) and Lyra & Umurhan (2019). For our model we expect the VSI to be quenched inwards of 20 au.…”
Section: The Inner Edge Of the Vsi Active Zonementioning
confidence: 96%
“…The dynamical states of protostellar disks during the first million years after their formation are crucial for understanding planet formation processes. As the coupling of the magnetic field to the gas in these dense and cold disks is believed to be weak (Turner et al 2014;Armitage 2019), it seems likely that various hydrodynamical instabilities play important roles, such as the Goldreich−Schubert−Fricke (GSF) instability (Goldreich & Schubert 1967;Fricke 1968), the convective instability (Cameron & Pine 1973), the Papaloizou−Pringle instability (Papaloizou & Pringle 1984), the baroclinic instability (Klahr & Bodenheimer 2003;Lesur ical timescale (Urpin & Brandenburg 1998;Nelson et al 2013;Lin & Youdin 2015;Richard et al 2016;Malygin et al 2017;Latter & Papaloizou 2018;Pfeil & Klahr 2019;Lyra & Umurhan 2019). Recent hydrodynamical simulations have found that the VSI develops in the non-linear regime to produce vortices (Richard et al 2016;Manger & Klahr 2018) due to the Rossby-Wave-Instability (Li et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In Flock et al (2017) we found a stress-to-pressure ratio of up to 0.1 for the net vertical magnetic flux case. For temperatures below the ionization threshold we chose stress-to-pressure ratios α DZ between 10 −3 and 5 × 10 −4 , to mimic the accretion activity either by hydrodynamical instabilities (Lyra & Umurhan 2019) or a magnetically driven wind (Béthune et al 2017). We note again that the increase in the stress-to-pressure ratio at the ionization transition has a direct impact on the surface density profile.…”
Section: Model Parametersmentioning
confidence: 99%